Parenting Styles and Parental Education Levels and Their Correlation with Students' Mathematics Learning Outcomes During the Covid 19 Pandemic - M. K. Pramana; I M. Suarjana (Journal of Psychology and Instruction, 2021)
This study aims to analyze the relationship between parenting styles and parental education levels on students' mathematics learning outcomes. This type of research is ex post facto. The population of this study was all fourth-grade elementary school students. Samples were taken using the proportional random sampling technique with a sample of 78 students. Data were collected by filling out a parenting style questionnaire by students who were the sample in the study. In contrast, data on parents' education level and students' mathematics learning outcomes were obtained through document recording. Data were analyzed by regression analysis technique. Regression analysis prerequisite tests include normality, linearity, and multicollinearity tests. After the prerequisite test is met, the next step is to test the hypothesis using simple regression, product-moment correlation, and multiple regression. The hypothesis testing results show a relationship between parenting styles and mathematics learning outcomes, there is a relationship between parents' education level on learning outcomes, and there is a relationship between parenting styles—parents’ education level on mathematics learning outcomes.